Toxins from Gliricidia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The leaves of Gliricidia sepium, the multipurpose leguminous tree commonly used in alley farming, contain a substance called coumarin. This can be converted to dicoumerol, a substance that is chemically so similar to Vitamin K that it interferes...